Pengaruh Aromaterapi Lavender terhadap Tingkat Nyeri Pasien Post Operasi Orif di RSUD Dr. H. Soewondo Kendal - Ririn Septrianingsih; Mohammad Arifin Noor; Suyanto Suyanto (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Fractures are conditions of discontinuation of bone or cartilage, either partially or completely, which often require surgical treatment. One of the commonly used procedures is Open Reduction Internal Fixation (ORIF), which is an open surgical procedure with the installation of fixation tools such as pins, screws, and plates to repair broken bones. This procedure generally causes postoperative pain that needs to be treated effectively. Pain management can be done through pharmacological and non-pharmacological approaches. Lavender aromatherapy is one of the non-pharmacological methods that has the potential to provide a relaxing and analgesic effect. This study aims to determine the effect of lavender aromatherapy on the level of pain in patients after ORIF surgery. The research method uses a qualitative approach with a Quasi Experiment design. The sampling technique was carried out in total sampling with a total of 28 respondents post-operative ORIF patients at Dr. H. Soewondo Kendal Hospital. The data were analyzed using the Wilcoxon test to determine the difference in pain levels before and after the administration of aromatherapy. The results showed a p value of 0.000, which indicated a significant influence between the administration of lavender aromatherapy on the reduction of the patient's pain level. The conclusion of this study is that lavender aromatherapy is effective in reducing the intensity of postoperative pain of ORIF, so that it can be used as an alternative to nonpharmacological therapy in postoperative pain management. This study recommends the integration of aromatherapy in nursing practice to improve patient comfort.